En torno a las composiciones litúrgicas latinas de la Hispania medieval en honor de Leandro de Sevilla (602) - Martín-Iglesias, José Carlos 1968- (2014)
The Latin hagiographic corpus around St. Leander of Seville has hardly been studied. This article provides a first study of Vitae s. Leandri preserved in manuscripts of Hispanic origin, and the editio princeps of two medieval Latin lives dedicated to the figure of this saint.
Keywords: Leandro, -- Santo, Arzobispo de Sevilla; Historiografía; Crítica textual; Liturgia